1998
DOI: 10.1105/tpc.10.12.2019
|View full text |Cite
|
Sign up to set email alerts
|

Guidance in Vitro of the Pollen Tube to the Naked Embryo Sac of Torenia fournieri

Abstract: The precise guidance of the pollen tube to the embryo sac is critical to the successful sexual reproduction of flowering plants. We demonstrate here the guidance of the pollen tube to the embryo sac in vitro by using the naked embryo sac of Torenia fournieri, which protrudes from the micropyle of the ovule. We developed a medium for culture of both the ovule and the pollen tube of T. fournieri and cocultivated them in a thin layer of solid medium. Although pollen tubes that had germinated in vitro passed naked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(144 citation statements)
references
References 40 publications
3
141
0
Order By: Relevance
“…In all species studied, synergid degeneration occurs on pollen tube penetration ( Jensen 1965;Russell 1996), and recent work with ablation experiments clearly demonstrated that the synergids are required for pollen tube penetration into the embryo sac (Higashiyama et al 2001). Further, embryo sacs with degenerated synergids fail to attract pollen tubes (Higashiyama et al 1998). As the synergid degenerates, an actin corona has been reported to develop in mature embryo sacs (Huang & Russell 1994), which has been shown to play a central part in the delivery of the male gametes to the egg cell and polar nucleus (Russsell 1996;Fu et al 2000) …”
Section: Successful Mating Is Preceded By a Synchronous Male-female Rmentioning
confidence: 96%
“…In all species studied, synergid degeneration occurs on pollen tube penetration ( Jensen 1965;Russell 1996), and recent work with ablation experiments clearly demonstrated that the synergids are required for pollen tube penetration into the embryo sac (Higashiyama et al 2001). Further, embryo sacs with degenerated synergids fail to attract pollen tubes (Higashiyama et al 1998). As the synergid degenerates, an actin corona has been reported to develop in mature embryo sacs (Huang & Russell 1994), which has been shown to play a central part in the delivery of the male gametes to the egg cell and polar nucleus (Russsell 1996;Fu et al 2000) …”
Section: Successful Mating Is Preceded By a Synchronous Male-female Rmentioning
confidence: 96%
“…In Torenia fournieri, pollen tubes are directly attracted to the exserted embryo sac in vitro (Higashiyama et al, 1998). Laser ablation experiments identified the source of the diffusible signal as the two synergid cells (Higashiyama et al, 2001).…”
mentioning
confidence: 99%
“…By mixing ovules of two species, one can critically examine whether pollen tubes sense the attraction signal of a different species under conditions in which they can surely respond to the attraction signal of their own species. In addition, the condition of the synergid cell is easily observed in the exserted embryo sac, but the attraction can only be examined in embryo sacs with complete synergid cells (the synergid is a fragile cell; Higashiyama et al, 1998). Ablation experiments using UV lasers are also possible in the exserted embryo sac, as shown in T. fournieri (Higashiyama et al, 2001), and can be used to confirm the role of the synergid cell in pollen tube attraction.…”
mentioning
confidence: 99%
“…The use of a style for pollen germination in Torenia is required to activate targeting of pollen tubes (Higashiyama et al 1998), but in Brachiaria this is not possible because of a barrier mechanism in the style. Potentially, this step may not be required, as in Gasteria (Willemse et al 1995), where free pollen is easy to handle, efficient and fully functional.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of in vitro fertilization in general and specifically in Brachiaria can be useful as a tool for plant breeding (Willemse et al 1995;Higashiyama et al 1998). Culture media are used to germinate pollen and to maintain the viability of the buds, or organs.…”
Section: Introductionmentioning
confidence: 99%